High-strength aluminum alloy conductor and preparation method thereof

By optimizing the raw material ratio and preparation process of aluminum alloy conductors, and using composite nanophase design and multi-stage aging technology, the problem of degradation of aluminum alloy conductors in high temperature, humidity or corrosive environments is solved, and the effects of high strength, excellent conductivity and corrosion resistance are achieved.

CN119956173APending Publication Date: 2025-05-09HEBEI YINGSHANG ALUMINUM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510313967.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In high-strength aluminum alloy conductors may decline in conductivity, strength and corrosion resistance in high-strength aluminum alloy conductors may be difficult to meet the needs of long-distance power transmission, aerospace, and new energy vehicles.

Method used

By optimizing the raw material ratio and preparation process, the composite addition of four elements: Sc, Yb, Zr, and Ti is used to form high-density and high-stability nano-precipitation phases, and a multi-stage aging process and continuous casting and rolling process are used to regulate the size and distribution of the precipitation phases and improve the strength and conductivity of the material.

Benefits of technology

It has achieved a significant improvement in the conductivity, strength and corrosion resistance of aluminum alloy conductors in high temperature, humid or corrosive environments, breaking through the performance bottleneck of traditional aluminum alloys in "strength-conductivity-corrosive resistance".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of aluminum alloy conductors, and provides a high-strength aluminum alloy conductor and a preparation method thereof. The high-strength aluminum alloy conductor is prepared from the following components in percentage by mass: 0.2 percent to 0.4 percent of Si, 0.5 percent to 0.7 percent of Mg, 0.3 percent to 0.5 percent of Ti, 0.3 percent to 0.5 percent of Zn, 0.1 percent to 0.15 percent of Zr, 0.05 percent to 0.1 percent of Sc, 0.05 percent to 0.15 percent of Yb, 0.01 percent to 0.03 percent of Sn, less than or equal to 0.15 percent of Fe, 0.003 percent to 0.005 percent of B and the balance of inevitable impurities and Al. According to the high-strength aluminum alloy conductor provided by the invention, by optimizing the raw material ratio and the preparation process, the conductivity, strength and corrosion resistance of the aluminum alloy conductor in a high-temperature, humid or corrosive environment are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy conductors, and in particular to a high-strength aluminum alloy conductor and a preparation method thereof. Background Art

[0002] Aluminum alloys are lightweight, high-strength alloy materials that are widely used in the wire and cable industry. High-strength aluminum alloy conductors are made by adding specific alloying elements to the aluminum matrix and undergoing a series of processing, deformation and heat treatment processes to obtain excellent strength, plasticity and electrical properties. This type of conductor material not only has a low density, but also exhibits good conductivity and corrosion resistance. It is an ideal choice to replace traditional copper conductors, especially in the fields of long-distance power transmission, aerospace and new energy vehicles.

[0003] When a high-strength aluminum alloy conductor is used in different environments, its performance may change. For example, in a high temperature, humid or corrosive environment, the conductivity, strength and corrosion resistance of the aluminum alloy conductor may decrease. Based on this, the present invention provides a high-strength aluminum alloy conductor and a preparation method thereof. Summary of the invention

[0004] The present invention provides a high-strength aluminum alloy conductor and a preparation method thereof, which improves the conductivity, strength and corrosion resistance of the aluminum alloy conductor in a high-temperature, humid or corrosive environment by optimizing the raw material ratio and the preparation process.

[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a high-strength aluminum alloy conductor, which is composed of the following components, by mass percentage: Si: 0.2%-0.4%, Mg: 0.5%-0.7%, Ti: 0.3%-0.5%, Zn: 0.3%-0.5%, Zr: 0.1%-0.15%, Sc: 0.05%-0.1%, Yb: 0.05%-0.15%, Sn: 0.01%-0.03%, Fe: ≤0.15%, B: 0.003%-0.005%, and the balance is unavoidable impurities and Al.

[0006] As a further technical solution, the aluminum alloy conductor is composed of the following components, in mass percentage: Si: 0.3%, Mg: 0.6%, Ti: 0.4%, Zn: 0.4%, Zr: 0.12%, Sc: 0.07%, Yb: 0.1%, Sn: 0.02%, Fe: ≤0.15%, B: 0.004%, and the balance is unavoidable impurities and Al.

[0007] In a second aspect, the present invention provides a method for preparing a high-strength aluminum alloy conductor, the steps comprising: (1) crushing the aluminum ingot into 10-20 mm blocks to obtain pretreated aluminum ingots; (2) adding Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy in sequence to the pretreated aluminum ingot, and finally adding Sn element and Al-B alloy for smelting; (3) Pass a mixed gas of argon and chlorine for 10-15 minutes to remove hydrogen; (4) Casting and rolling are carried out at a temperature of 690-710°C, and the thickness of the cast strip is 7-9 mm; (5) The cast strip is subjected to hot rolling, cold drawing, annealing and aging treatment.

[0008] As a further technical solution, the cooling rate during the casting is 100-140°C / s.

[0009] As a further technical solution, the conditions during smelting include: a temperature of 735-745°C, a vacuum degree of 0.6×10 -2 Pa -1 ×10 -2 Pa, and stir for 20-30 min under electromagnetic stirring at a frequency of 13-15 kHz.

[0010] As a further technical solution, the volume ratio of argon gas to chlorine gas is 99-99.5:0.5-1.

[0011] As a further technical solution, the initial rolling temperature of the hot rolling is 480-500°C, the total deformation is 68%-72%, the deformation per pass is ≤15%, and the final rolling temperature is 300-320°C.

[0012] As a further technical solution, the cold drawing step includes at least 4 drawing passes, with a deformation amount of 19%-21% in each pass.

[0013] As a further technical solution, the annealing step needs to be performed after each drawing, the annealing temperature is 280-320° C., and the annealing time is 25-35 min.

[0014] As a further technical solution, the aging step includes: maintaining at 100-110°C for 5-6 hours, maintaining at 175-185°C for 9-11 hours, and maintaining at 240-260°C for 60-70 minutes.

[0015] The working principle and beneficial effects of the present invention are: In the present invention, by adding Sc, Yb, Zr, and Ti four elements in combination, a high-density, high-stability nano-precipitated phase is formed, wherein the Sc element can form an Al3Sc nano-phase, and these nano-phases, as strengthening phases, can effectively improve the strength of the material. At the same time, Yb and Zr jointly inhibit grain coarsening at high temperatures and improve the heat resistance of the material. The Ti element plays a role in pinning dislocations by forming a TiB2 phase, further enhancing the strength of the material. This quaternary composite nano-phase design achieves high-density distribution and high-temperature stability of the nano-precipitated phase, thereby breaking through the performance bottleneck of traditional aluminum alloys in "strength-conductivity-corrosion resistance".

[0016] The present invention adopts a multi-stage aging process to finely control the size of the precipitated phase. The multi-stage aging process includes maintaining different temperatures for different times, which helps the precipitated phase to form precipitates of different sizes and shapes at different stages. By finely controlling the size and distribution of these precipitates, the strength and conductivity of the material can be further optimized. Compared with single-stage aging, multi-stage aging can more effectively control the growth of the precipitated phase, avoid excessive precipitates causing increased electron scattering, and thus reduce conductivity.

[0017] The present invention adopts a continuous casting and rolling process to increase the dislocation density of the material and enhance the strength; the continuous casting and rolling process can be rolled immediately after casting, and the heat energy and dislocations generated during the casting process are utilized to further refine the grains and increase the dislocation density through rolling. This process can effectively improve the strength of the material while maintaining a high electrical conductivity. Compared with ordinary rolling, the continuous casting and rolling process can more effectively utilize the heat energy in the casting process, reduce energy consumption, and improve production efficiency.

[0018] The technical solution of the present invention balances strength and conductivity by reducing the content of Mg while ensuring strength. Although Mg is a commonly used strengthening element in aluminum alloys, excessive Mg content will increase solid solution damage, thereby reducing conductivity. The present invention reduces the content of Mg and uses other strengthening elements (such as Sc, Yb, Zr, Ti) to compensate, thereby achieving high conductivity while ensuring strength.

[0019] The present invention adopts electromagnetic stirring during the smelting process to improve the homogenization of the components. Electromagnetic stirring can generate strong convection during the smelting process, making the components in the melt more uniform. This homogenization helps to improve the performance stability of the material and reduce the performance dispersion. At the same time, electromagnetic stirring can also promote the discharge of gas and inclusions and improve the purity of the material. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 In the present embodiment, a high-strength aluminum alloy conductor is provided. The aluminum alloy conductor consists of the following components, in mass percentage: Si: 0.3%, Mg: 0.6%, Ti: 0.4%, Zn: 0.4%, Zr: 0.12%, Sc: 0.07%, Yb: 0.1%, Sn: 0.02%, Fe: 0.1%, B: 0.004%, and the remainder is inevitable impurities and Al.

[0022] The method for preparing the high-strength aluminum alloy conductor comprises the following steps: (1) crushing the aluminum ingot into 15 mm blocks to obtain pretreated aluminum ingots; (2) Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy, and finally Sn element and Al-B alloy are added to the pretreated aluminum ingot in sequence and smelted at a temperature of 740°C. The vacuum degree during smelting is 0.8×10 -2 Pa, and kept stirring for 25 min under electromagnetic stirring at a frequency of 14 kHz; (3) Passing a mixed gas of argon and chlorine in a volume ratio of 99.2:0.8 for 12 minutes to remove hydrogen; (4) Casting and rolling were carried out at a temperature of 700°C, the thickness of the cast strip was 8 mm, and the cooling rate was 120°C / s; (5) hot rolling the cast strip, with an initial rolling temperature of 490°C, a total deformation of 70%, a deformation of 15% per pass, and a final rolling temperature of 310°C; (6) The hot-rolled alloy material was drawn five times, with a deformation of 20% in each pass; annealing was performed after each drawing, with an annealing temperature of 300°C and an annealing time of 30 min; (7) The drawn and annealed alloy material is subjected to aging treatment by maintaining it at 105°C for 5.5 hours, at 180°C for 10 hours, and at 250°C for 65 minutes.

[0023] Example 2 In the present embodiment, a high-strength aluminum alloy conductor is provided. The aluminum alloy conductor consists of the following components, in percentage by mass: Si: 0.2%, Mg: 0.5%, Ti: 0.3%, Zn: 0.3%, Zr: 0.1%, Sc: 0.05%, Yb: 0.05%, Sn: 0.01%, Fe: 0.15%, B: 0.003%, and the remainder is unavoidable impurities and Al.

[0024] The method for preparing the high-strength aluminum alloy conductor comprises the following steps: (1) crushing the aluminum ingot into 10 mm blocks to obtain pretreated aluminum ingots; (2) Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy, and finally Sn element and Al-B alloy are added to the pretreated aluminum ingot in sequence and smelted at a temperature of 735°C. The vacuum degree during smelting is 0.6×10 -2 Pa, and kept stirring for 20 min under electromagnetic stirring at a frequency of 13 kHz; (3) Passing a mixed gas of argon and chlorine with a volume ratio of 99:1 for 10 minutes to remove hydrogen; (4) Casting and rolling were carried out at a temperature of 700°C, the thickness of the cast strip was 8 mm, and the cooling rate was 120°C / s; (5) hot rolling the cast strip, with an initial rolling temperature of 490°C, a total deformation of 70%, a deformation of 15% per pass, and a final rolling temperature of 310°C; (6) The hot-rolled alloy material was drawn five times, with a deformation of 20% in each pass; annealing was performed after each drawing, with an annealing temperature of 300°C and an annealing time of 30 min; (7) The drawn and annealed alloy material is subjected to aging treatment by maintaining it at 100°C for 5 hours, at 175°C for 9 hours, and at 240°C for 60 minutes.

[0025] Example 3 In the present embodiment, a high-strength aluminum alloy conductor is provided. The aluminum alloy conductor consists of the following components, in percentage by mass: Si: 0.4%, Mg: 0.7%, Ti: 0.5%, Zn: 0.5%, Zr: 0.15%, Sc: 0.1%, Yb: 0.15%, Sn: 0.03%, Fe: 0.15%, B: 0.005%, and the remainder is unavoidable impurities and Al.

[0026] The method for preparing the high-strength aluminum alloy conductor comprises the following steps: (1) crushing the aluminum ingot into 20 mm blocks to obtain pretreated aluminum ingots; (2) Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy, and finally Sn element and Al-B alloy are added to the pretreated aluminum ingot in sequence and smelted at a temperature of 745°C. The vacuum degree during smelting is 1×10 -2 Pa, and kept stirring for 30 min under electromagnetic stirring at a frequency of 15 kHz; (3) Passing a mixed gas of argon and chlorine in a volume ratio of 99.5:0.5 for 15 minutes to remove hydrogen; (4) Casting and rolling were carried out at a temperature of 700°C, the thickness of the cast strip was 8 mm, and the cooling rate was 120°C / s; (5) hot rolling the cast strip, with an initial rolling temperature of 490°C, a total deformation of 70%, a deformation of 15% per pass, and a final rolling temperature of 310°C; (6) The hot-rolled alloy material was drawn five times, with a deformation of 20% in each pass; annealing was performed after each drawing, with an annealing temperature of 300°C and an annealing time of 30 min; (7) The drawn and annealed alloy material is subjected to aging treatment by maintaining it at 110°C for 6 hours, at 185°C for 11 hours, and at 260°C for 70 minutes.

[0027] Example 4 In the present embodiment, a high-strength aluminum alloy conductor is provided. The aluminum alloy conductor consists of the following components, in percentage by mass: Si: 0.2%, Mg: 0.7%, Ti: 0.3%, Zn: 0.5%, Zr: 0.1%, Sc: 0.1%, Yb: 0.05%, Sn: 0.03%, Fe: 0.15%, B: 0.003%, and the remainder is unavoidable impurities and Al.

[0028] The method for preparing the high-strength aluminum alloy conductor comprises the following steps: (1) crushing the aluminum ingot into 20 mm blocks to obtain pretreated aluminum ingots; (2) Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy, and finally Sn element and Al-B alloy are added to the pretreated aluminum ingot in sequence and smelted at a temperature of 735°C. The vacuum degree during smelting is 1×10 -2 Pa, and kept stirring for 30 min under electromagnetic stirring at a frequency of 13 kHz; (3) Passing a mixed gas of argon and chlorine with a volume ratio of 99:1 for 10 minutes to remove hydrogen; (4) Casting and rolling were carried out at a temperature of 700°C, the thickness of the cast strip was 8 mm, and the cooling rate was 120°C / s; (5) hot rolling the cast strip, with an initial rolling temperature of 490°C, a total deformation of 70%, a deformation of 15% per pass, and a final rolling temperature of 310°C; (6) The hot-rolled alloy material was drawn five times, with a deformation of 20% in each pass; annealing was performed after each drawing, with an annealing temperature of 300°C and an annealing time of 30 min; (7) The drawn and annealed alloy material is subjected to aging treatment by maintaining it at 110°C for 5 hours, at 185°C for 9 hours, and at 260°C for 70 minutes.

[0029] Example 5 Adjustments were made based on Example 1. Unlike Example 1, Example 5 did not undergo single-stage aging, but was maintained at 180° C. for only 10 h.

[0030] Example 6 Adjustments are made based on Example 1. Unlike Example 1, Example 6 does not include electromagnetic stirring.

[0031] Example 7 Adjustments were made based on Example 1. The difference from Example 1 was that the deformation amount of each hot rolling pass in Example 7 was 25%.

[0032] Comparative Example 1 Adjustments were made based on Example 1. The difference from Example 1 was that no Sc was added to the components in Comparative Example 1.

[0033] Comparative Example 2 Adjustments were made based on Example 1. The difference from Example 1 was that no Yb was added to the components in Comparative Example 2.

[0034] Comparative Example 3 Adjustments were made based on Example 1. The difference from Example 1 was that no Zr was added to the components in Comparative Example 3.

[0035] Comparative Example 4 Adjustments were made based on Example 1. The difference from Example 1 was that no Ti was added to the components in Comparative Example 4.

[0036] Comparative Example 5 Adjustments were made on the basis of Example 1. Different from Example 1, the content of Mg in Comparative Example 5 was 1%.

[0037] Test Example 1: The aluminum alloy conductors prepared in the above-mentioned Examples 1-7 and Comparative Examples 1-5 were subjected to the following tests: 1. Tensile strength: GB / T 228.1-2021; 2. Electrical conductivity: GB / T 3048.2-2007; 3. Corrosion resistance: GB / T 10125-2021 neutral salt spray test, the experimental conditions are 35°C, 5% mass concentration NaCl aqueous solution.

[0038] The results are shown in Table 1 below: Table 1

[0039] Combined with the above data, it can be seen that comparative examples 1-4 show that the lack of any element of Sc / Yb / Zr / Ti leads to a decrease in strength and corrosion resistance, proving that the quaternary composite is the core of breaking through the performance bottleneck. Sc-Yb-Zr-Ti has a synergistic effect, in which Sc provides nanophase nucleation sites, Yb / Zr inhibits high-temperature grain boundary migration, and TiB2 pins dislocations. The strength and conductivity of Example 5 both decrease, proving the key role of multi-level aging in regulating the size of the precipitated phase; the conductivity of Comparative Example 5 decreases, verifying that the low Mg design of this scheme can balance strength and conductivity; Examples 1-4 are significantly better than the comparative examples in terms of strength, conductivity, and corrosion resistance, breaking the dilemma that traditional aluminum alloys cannot have both "strength-conductivity-corrosion resistance".

[0040] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength aluminum alloy conductor, characterized in that: The aluminum alloy conductor is composed of the following components in mass percentage: Si: 0.2%-0.4%, Mg: 0.5%-0.7%, Ti: 0.3%-0.5%, Zn: 0.3%-0.5%, Zr: 0.1%-0.15%, Sc: 0.05%-0.1%, Yb: 0.05%-0.15%, Sn: 0.01%-0.03%, Fe: ≤0.15%, B: 0.003%-0.005%, and the balance is inevitable impurities and Al.

2. A high-strength aluminum alloy conductor according to claim 1, characterized in that: The aluminum alloy conductor is composed of the following components in percentage by mass: Composition: Si: 0.3%, Mg: 0.6%, Ti: 0.4%, Zn: 0.4%, Zr: 0.12%, Sc: 0.07%, Yb: 0.1%, Sn: 0.02%, Fe: ≤0.15%, B: 0.004%, and the balance is inevitable impurities and Al.

3. A method for preparing a high-strength aluminum alloy conductor as claimed in claim 1 or 2, characterized in that the steps include: (1) crushing the aluminum ingot into 10-20 mm blocks to obtain pretreated aluminum ingots; (2) adding Al-Si alloy, Mg element, Zn element, Al-Ti alloy, Al-Zr alloy, Al-Sc alloy, Al-Yb alloy in sequence to the pretreated aluminum ingot, and finally adding Sn element and Al-B alloy for smelting; (3) Pass a mixed gas of argon and chlorine for 10-15 minutes to remove hydrogen; (4) Casting and rolling are carried out at a temperature of 690-710°C, and the thickness of the cast strip is 7-9 mm; (5) The cast strip is subjected to hot rolling, cold drawing, annealing and aging treatment.

4. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The cooling rate during the casting and rolling is 100-140°C / s.

5. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The conditions during the smelting process include: a temperature of 735-745°C, a vacuum degree of 0.6×10 -2 Pa -1 ×10 -2 Pa, and stir for 20-30 min under electromagnetic stirring at a frequency of 13-15 kHz.

6. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The volume ratio of the argon gas to the chlorine gas is 99-99.5:0.5-1.

7. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The initial rolling temperature of the hot rolling is 480-500°C, the total deformation is 68%-72%, the deformation of each pass is ≤15%, and the final rolling temperature is 300-320°C.

8. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The cold drawing step includes at least 4 drawing passes, and the deformation amount of each pass is 19%-21%.

9. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The annealing step needs to be performed after each drawing, the annealing temperature is 280-320° C., and the annealing time is 25-35 min.

10. The method for preparing a high-strength aluminum alloy conductor according to claim 3, characterized in that: The aging step includes: maintaining at 100-110° C. for 5-6 hours, maintaining at 175-185° C. for 9-11 hours, and maintaining at 240-260° C. for 60-70 minutes.

Citation Information

Cited By

  • Anti-fracture cold forging forming method for steering pull rod of new energy vehicle

    CN120644610A

  • High-strength alloy conductor and preparation method thereof

    CN121034697A